Ability of PROMIS Pediatric Measures to Detect Change in Children With Cerebral Palsy Undergoing Musculoskeletal Surgery. Issue 7 (October 2016) - Mulcahey, Mary J.; Haley, Stephen M.; Slavin, Mary D.; Kisala, Pamela A.; Ni, Pengsheng; Tulsky, David S.; Jette, Alan M.
Abstract : Background: The Patient Reported Outcomes Measurement Information System (PROMIS) was developed to provide patient-reported outcome measures that are designed as being universally relevant across health conditions, low burden, and precise. A major problem for research and clinical practice in cerebral palsy (CP) is the void of outcomes instruments that are capable of evaluating the wide range of abilities and broad age spectrum inherent in this clinical population. Given the tremendous potential of PROMIS, the research questions for this study were "How do PROMIS pediatric computer adaptive tests and short forms detect change in children with CP following elective musculoskeletal surgery?" and "How do PROMIS instruments compare to the Pediatric Quality of Life Inventory Cerebral Palsy Module Version 3.0 (PedsQL CP), Pediatric Outcomes Data Collection Instrument (PODCI), the Timed Up and Go (TUG), and the Gross Motor Functional Measure (GMFM)." Methods: PROMIS Pediatric computer adaptive tests and short forms and the PedsQL, PODCI, TUG, and GMFM were administered before and after surgery. Effect size (ES) and standardized response mean (SRM) were calculated. Floor and ceiling effects were evaluated and, exposure rates for the PROMIS item banks were examined. Results: ES and SRM for all PROMIS Pediatric Measures were nonsignificant. PedsQL CP detected significant, positive change in mobility at 6 (ES=0.26; SRM=0.31) and 12 (ES=0.36; SRM=0.36) months; pain at 12 months (ES=0.29; SRM=0.34); and fatigue at 6 (ES=0.24; SRM=0.22) and 12 (ES=0.36; SRM=0.41) months. Significant negative changes were detected by the PODCI (ES=−0.20; SRM=−0.26), GMFM (ES=−0.13; SRM=−0.24), and TUG (ES=−0.29; SRM=−0.25). Ceiling effects were high. Exposure to an appropriate range of the PROMIS Mobility item bank was limited. Conclusions: PROMIS measures were less able to detect change than other measures. PROMIS measures may be improved by tailoring start/stop rules or by adding items to include content appropriate for children with mobility impairments. Level of Evidence: Level III—diagnostic study.